Panggilan dan Tugas Bapak-Ibu Baptis Dalam Gereja Katolik - Blasius Superma Yese (Jurnal Magistra, 2024)
The sacrament of Baptism is often referred to as the gateway to enter the community of believers in Jesus, especially in the Catholic Church, because it is the first sacrament received. Other sacraments can only be received after receiving the sacrament of Baptism. By receiving the sacrament of Baptism, a person can receive his rights and obligations as a Catholic. In the rite of receiving the sacrament of Baptism, one of the important parties to be considered is the godparents, or often also called the godfather or godmother. Its presence does not merely fulfil the requirements of formality, which is then recorded in the Baptismal Book or Liber Baptizatorum; but it has a certain role before and after the celebration of baptism.